Health value added of healthcare entities - Ejsmont, Wiktor; Łyko, Janusz (Zdrowotna wartość dodana jednostek służby zdrowia, 2020)
The paper deals with an evaluation of the quality of services provided by healthcare organizations. First, an index representing a patient’s health condition is described, then its changes before and after being treated by a given entity are employed as a criterion to assess the operations of this entity. The index of a patient’s health condition is based on the theory of survival analysis, while a model of random effects is used to determine the quality of services based on health value added
Econometrics = Ekonometria, 2020, Vol. 24, No. 3, s. 51-58
Keywords: effectiveness; health value added; analysis of panel data; measurement of health; efektywność; zdrowotna wartość dodana; analiza danych panelowych; pomiar zdrowia